A Study in Vendor Development Micro & Small Enterprises Supplies to PSUs in Hyderabad and Visakhapatnam - Rajeshwari, K. R. (Indian Journal of Marketing, 2008)
Marketing has always been a bottleneck operation in the business operations of a small-scale enterprise. A small-scale enterprise is saddled with many inhibiting factors, where market operations are concerned. Unlike large enterprises, where there is a separate Marketing department, headed by a Marketing Manager, with many persons assisting him, and a large budget for all kinds of marketing activities, including advertisement, a single person or a few persons manage the entire range of operations in a Small-scale unit. In this scenario, reaching out to the market, accessing information, identifying prospective buyers, executing job orders, planning marketing strategies, timely realization of sales amounts etc become very taxing for the entrepreneur. Consequently, the entrepreneur is unable to pay due attention towards planning marketing strategies, and exploring new markets. However, the entrepreneur has to realize the importance of marketing his goods to the right buyer, and has to focus on his product meeting the requirement of the customers, be it regarding quality, timely delivery, price or quantity